Introducing statistics - Upton, Graham (Oxford University Press, 1998)
Introducing Statistics has been revised to meet the requirements of all the new A Level specifications. It covers in one volume all the statistics required by students taking single-subject Advanced Level Mathematics and also provides the basis for a first course in statistics in higher education. This is a highly accessible resource, supported by clear illustrations, nearly 200 worked examples, and packed with examination style questions. Suggestions for practical work and for calculator and computer exercises are included..